Healthy tree / Sakinah Ahmad Kamal Ariffin ... [et al.] - Kamal Ariffin, Sakinah; Zaini, Zaidatul Hidayu; Seni, Suhaila; Zainal, Nur Fatin Afifa; Arzemi, Nur Shafinas; Norihsan, Nur Adila Akma (2019)
HEAL THY TREE is a company which focuses 011.. healthy dessert production in Malaysia. Ice cream and smoothies are the most popular dessert and are always on demand anytime and anywhere. The light and soft texture gives the delicious taste to this ice cream and smoothies to be marketable product as people love simple things especially food. Moreover, the simple steps and ingredients give a lot of benefits to our company and we are highly confident that our market can be easily developed and spread in Malaysia. To make it more attractive and interesting, we decided to make our dessert go around Johor Bahru to give every people in the Johor Bahru area to taste our product. Thus, give some innovation by implying our creativity and modem element in this ice cream and smoothies making. Nowadays, flavor is one of the important things in any products making so a new different flavour might be a new attraction to people. We have created three great flavor each for our ice cream and smoothies. We have done some research that Malaysia people nowadays are focuses on getting fit and healthy. Normally people who work out and on strict diet are stress looking for dessert that does not affect their calories intake that could destroy their diet. So, with our new innovation, they can just simply eat our product without feeling guilty about their diets